Onset of herbivore-induced resistance in systemic tissue primed for jasmonate-dependent defenses is activated by abscisic acid - Vos, Irene A.; Verhage, Adriaan; Schuurink, Robert C.; Watt, Lewis G.; Pieterse, Corné M.; Van Wees, Saskia C. (Frontiers in Plant Science, 2013)
In Arabidopsis, the MYC2 transcription factor on the one hand and the AP2/ERF transcription factors ORA59 and ERF1 on the other hand regulate distinct branches of the jasmonic acid (JA) signaling pathway in an antagonistic fashion, co-regulated by abscisic acid (ABA) and ethylene, respectively. Feeding by larvae of the specialist herbivorous insect Pieris rapae (small cabbage white butterfly) results in activation of the MYC-branch and concomitant suppression of the ERF-branch in insect-damaged leaves. Here we investigated differential JA signaling activation in undamaged systemic leaves of P. rapae-infested plants. We found that the MYC2 transcription factor gene was induced both in the local insect-damaged leaves and the systemic undamaged leaves of P. rapae-infested Arabidopsis plants. However, in contrast to the insect-damaged leaves, the undamaged tissue did not show activation of the MYC-branch marker gene VSP1. Comparison of the hormone signal signature revealed that the levels of JA and (+)-7-iso-jasmonoyl-L-isoleucine raised to similar extents in locally damaged and systemically undamaged leaves, but the production of ABA and the JA precursor 12-oxo-phytodienoic acid was enhanced only in the local herbivore-damaged leaves, and not in the distal undamaged leaves. Challenge of undamaged leaves of pre-infested plants with either P. rapae larvae or exogenously applied ABA led to potentiated expression levels of MYC2 and VSP1, with the latter reaching extremely high expression levels. Moreover, P. rapae-induced resistance, as measured by reduction of caterpillar growth on pre-infested plants, was blocked in the ABA biosynthesis mutant aba2-1, that was also impaired in P. rapae-induced expression of VSP1. Together, these results suggest that ABA is a crucial regulator of herbivore-induced resistance by activating primed JA-regulated defense responses upon secondary herbivore attack in Arabidopsis.